Turkey - Country Economic Memorandum : Volume 2. Sustaining High Growth, Selected Issues - World Bank (Washington, DC, 2012)
This Country Economic Memorandum (CEM), prepared in collaboration with the Turkish authorities, summarizes recent accomplishments in achieving high growth and analyzes remaining public policy challenges and options available to the authorities to meet these challenges. The country seeks to double the nominal per capita income of its population by 2013. It wants this rapid growth to be inclusive of all segments of society, regions, and economic sectors-especially through improved labor market performance leading to more and better jobs in the economy. At the same time, the authorities want to improve the quality of public services which they see as an important complement to economic growth in improving quality of life. They also believe that the potentially negative environmental consequences of the period of rapid growth ahead need to be managed so that the positive welfare gains from higher per capita income levels do not become eroded by environmental nuisances. Turkey has succeeded in restoring macroeconomic stability and rapid growth, it has been recovering from crisis in 2001 and grew at 7.5 percent per year on average during 2002-2006. In addition, certain dimensions of public sector governance are instrumental in improving quality of life and promoting competitiveness in Turkey including, for example, food safety and environmental protection. Further strengthening of the legal framework and institutions fighting corruption could improve the investment climate, the efficiency of the public sector, and popular support to further reforms, and continuous macroeconomic stability is a necessary (but not sufficient) condition for sustainable growth. Strong fiscal discipline and monetary policy have reduced chronic inflation to below 10 percent in 2005. Public debt has also been reduced and its sustainability has improved. Accordingly, the resilience of the Turkish economy to shocks has improved as demonstrated by the rapid recovery from turmoil in international markets in the summer of 2006 and, more recently, in the summer-autumn of 2007.